2018
DOI: 10.1111/imm.12895
|View full text |Cite
|
Sign up to set email alerts
|

Importance of B cells to development of regulatory T cells and prolongation of tissue allograft survival in recipients receiving autologous bone marrow transplantation

Abstract: We previously showed that congenic bone marrow transplantation (BMTx) post myeloablation augmented tissue allograft survival in association with increased regulatory T (Treg) cells of both host and bone marrow donor origin. Regulatory B (Breg) cells can also modulate T-cell immunity and B cells may be implicated in the development of Treg cells. Accordingly, we explored the effect of B-cell depletion in vivo on augmented graft survival post BMTx. C57BL/6 mice received BALB/c skin allografts followed 7 days lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Our data show that depletion of both CD4 + and CD8 + T cells post administration of anti-idiotype and immune Ig abolishes the suppression seen-the effect was most marked with combined CD4 and CD8 depletion. Most interestingly, using mAbs shown elsewhere to expand CD25 + Treg [22, 25, 26], we document increased suppression of Th2 responses by infusion of these mAbs after first commencing treatment with anti-idiotype and immune Ig. We suggest these data reflect an important role for perturbation of immune regulatory networks using homologous or heterologous anti-idiotype Ig and immune Ig in suppression of Th2 immunity, and thus potentially allergic responses, in naïve and sensitized hosts.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our data show that depletion of both CD4 + and CD8 + T cells post administration of anti-idiotype and immune Ig abolishes the suppression seen-the effect was most marked with combined CD4 and CD8 depletion. Most interestingly, using mAbs shown elsewhere to expand CD25 + Treg [22, 25, 26], we document increased suppression of Th2 responses by infusion of these mAbs after first commencing treatment with anti-idiotype and immune Ig. We suggest these data reflect an important role for perturbation of immune regulatory networks using homologous or heterologous anti-idiotype Ig and immune Ig in suppression of Th2 immunity, and thus potentially allergic responses, in naïve and sensitized hosts.…”
Section: Introductionmentioning
confidence: 65%
“…We [25, 26] and others [22, 28] have suggested that antibodies made against a molecule, TNFRSF25, expressed at the cell surface of CD4 + CD25 + Tregs may augment immunoregulation by putative Tregs in vivo-at least one such study has reported this molecule enhanced regulation of allergic immunity [22]. We have reported on production of several rat mAbs to a peptide of TNFRSF25 common to both the human and mouse molecules and observed by FACS and ELISA (with plate-bound cells) significant binding of several mAbs to enriched CD4 + Tregs.…”
Section: Resultsmentioning
confidence: 99%
“…At present, autologous HSCT has also been widely used in various types of liver cirrhosis, improving liver function in varying degrees ( 106 109 ). Coupled with the study of transplant animal models, these studies provide abundant theoretical basis for expanding autologous HSCT application in organ transplantation ( 110 112 ).…”
Section: Hematopoietic Stem Cell Transplantation (Hsct) For the Inducmentioning
confidence: 99%
“…105 In another study, depletion of total B cells before the establishment of EAE lead to exacerbated disease symptoms, but adoptive transfer of splenic IL-10-producing B cells before EAE induction normalized the disease progression, suggesting that these cells had a protective role in the onset of this central nervous system (CNS) pathology. 108 The direct engagement of CD1d high CD5 + B10 with Tregs through CD5 and CD72 has shown to induce their expansion and homeostasis. 106 In a murine model of rheumatoid arthritis (RA) induced by methylated BSA in mice deficient in Wiskott-Aldrich syndrome protein (WASp), which is characterized by exacerbated inflammatory activity and reduced Treg and Breg populations along with an increased number of Th17 inflammatory lymphocytes, the adoptive transfer of Bregs isolated from WT mice was able to restore the balance.…”
Section: The Immunomodulatory Function Of Il-10 Produced By B Cellsmentioning
confidence: 99%
“…107 In a different animal model of congenic bone marrow transplantation (BMTx), in vivo adoptive transfer of B cells after myeloablation showed increased allograft survival through donor-specific Treg development. 108 The direct engagement of CD1d high CD5 + B10 with Tregs through CD5 and CD72 has shown to induce their expansion and homeostasis. 109 In turn, Tregs were able to induce the expansion of IL-10-producing B cells through reciprocal interactions with the same two molecules.…”
Section: The Cross Talk Between Bregs and Other Immune Cells B Cellmentioning
confidence: 99%